1998
DOI: 10.1152/ajpheart.1998.274.1.h139
|View full text |Cite
|
Sign up to set email alerts
|

Rostral ventrolateral medullary opioid receptor activation modulates pressor response to muscle contraction

Abstract: The effects of an opioid agonist, [d-Ala2]methionine enkephalinamide (DAME), administered into the rostral ventrolateral medulla (rVLM) or caudal ventrolateral medulla (cVLM) on cardiovascular responses to isometric muscle contraction were determined in anesthetized rats. A 30-s contraction evoked by tibial nerve stimulation increased mean arterial pressure (MAP) and heart rate (HR) by 34 ± 6 mmHg and 40 ± 7 beats/min, respectively, with a developed tension of 322 ± 30 g, after bilateral insertion of microdial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…For example, microinjection of opioid agonists into the rVLM produces profound hypotension (47) and decreases in BP and HR in normotensive, chronic stressinduced hypertensive and spontaneously hypertensive rats, whereas naloxone injected into the rVLM blocks these responses. Furthermore, injection of opioid agonists into the rVLM inhibits BP responses to carotid occlusion and muscular exercise (8,31,47). These studies suggest that opioids in the rVLM have the potential to inhibit premotor sympathetic cardiovascular outflow.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, microinjection of opioid agonists into the rVLM produces profound hypotension (47) and decreases in BP and HR in normotensive, chronic stressinduced hypertensive and spontaneously hypertensive rats, whereas naloxone injected into the rVLM blocks these responses. Furthermore, injection of opioid agonists into the rVLM inhibits BP responses to carotid occlusion and muscular exercise (8,31,47). These studies suggest that opioids in the rVLM have the potential to inhibit premotor sympathetic cardiovascular outflow.…”
Section: Discussionmentioning
confidence: 80%
“…Opioid neurotransmitters in the rVLM are capable of regulating sympathetic outflow and, ultimately, cardiovascular function (8,44,47). For example, microinjection of opioid agonists into the rVLM produces profound hypotension (47) and decreases in BP and HR in normotensive, chronic stressinduced hypertensive and spontaneously hypertensive rats, whereas naloxone injected into the rVLM blocks these responses.…”
Section: Discussionmentioning
confidence: 99%
“…A migration of fentanyl sufficient to reach the brainstem would certainly negate the significance of our findings because the direct effect of fentanyl on medullary opioid receptors is recognized to affect neurons involved in cardiovascular (Sun et al . 1996; Caringi et al . 1998) and ventilatory (Lalley, 2008) control.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two studies have suggested a tonically active, inhibitory input to the CVL (Badoer and Chalmers, 1992) and the RVL (Sun et al, 1996). However, a recent study investigating the modulation by opioids of the cardiovascular responses to static muscle contraction has shown that microdialysis of NAL into the CVL or the RVL did not alter baseline mean arterial pressure or heart rate (Caringi et al, 1998). Our results showing a significant increase in Fos-LI in the RVL, thus, are in good agreement with the finding that NAL alone increases blood pressure and heart rate when injected into the RVL in normal rats (Sun et al, 1996).…”
Section: Is There a Tonic Opioid Control Of Cardiorespiratory Functions?mentioning
confidence: 99%